From Early Interest to Career Persistence: Understanding and Supporting STEM Pathways - Manuela Paechter; Silke Luttenberger; Christine R. Starr; Erin Mackenzie; Bernhard Ertl (MDPI AG, 2024)
Knowledge, competencies, and reflective attitudes regarding STEM (science, technology, engineering, and mathematics) are essential for navigating global and societal changes in the economy and workforce [...]